Canada : 2018 Article IV Consultation-Press-Release; Staff Report; and Statement by the Executive Director for Canada. (IMF Staff Country Reports; Country Report, 2018)
The economy has continued to perform well, but trade tensions, uncertainty about the outcome of NAFTA negotiations and the impact of the U.S. Tax Cuts and Jobs Act on Canada's competitiveness are casting a shadow over the outlook.